The effect of household and enterprise credit on current account balance: Evidence from the Republic of North Macedonia - Egzona Hani Selimi; Milan Eliskovski (National Bank of the Republic of North Macedonia, 2018)
The empirical literature points the financial intermediation, measured by the level of credits relative to GDP in the economy, as one of the factors which affects the current account dynamics in a given country. This paper tries to estimate and then quantify the possible impact that household and enterprise credits have on the current account deficit in North Macedonia. The motivation stems from the expectation that different kind of borrowers might vary in terms of the use of credit and thus might have different effects on macroeconomic variables. The results we get by using a vector error correction model (VECM) and data covering the 2005q1-2017q3 period, suggest that credits allocated to the household sector have a negative impact on the current account balance, while the enterprise credits have a positive and statistically significant effect on the external balance. The findings are in line with our prior expectation, given the import pressures that households' credits might induce and the positive impact that corporate credit might have on the overall productivity and competitiveness of the economy. The study is policy-relevant as it provides quantification on the effects that different types of credits might have on the current account balance.
Keywords: F32; F41; F14; E51; 330; household credit; enterprise/corporate credit; current account balance; current account deficit